The Potency of Goat Milk in Reducing the Induced Neurotoxic Effects of Valproic Acid in Rat Pups as a Rodent Model of Autism Spectrum Disorder - Alhanouf Mohammed Al-dossari; Laila Naif Al-Harbi; Norah M. Al-Otaibi; Abdullah Almubarak; Ahmed Tayseer Almnaizel; Ghedeir M. Alshammari; Ghalia Shamlan; Ali A. Alshatwi; Afaf El-Ansary (Metabolites, 2023)
Autism spectrum disorder (ASD) is a progressively prevalent neurodevelopmental disorder with substantial clinical heterogeneity. Despite the considerable interest in dietary interventions, no consensus has been reached regarding the optimal nutritional therapy. The present study aimed to investigate the possible positive effect of goat’s milk (GM) compared to cow’s milk (CM) on ASD autistic features in a valproic acid (VPA; 600 mg/kg)-induced white albino rat model of autism. All tests were conducted on rats that were divided into four groups (n = 15/group): control with goat milk (GM) treatment, control with cow milk (CM) treatment, autistic with goat milk (GM) treatment, and autistic with cow milk treatment. The casein levels were also measured in GM and CM. Social behavior was assessed by three-chambered sociability to test social interaction after the intervention. After 15 days of intervention, selected biomarkers, such as glutathione (GSH), thiobarbituric acid reactive substance (TBARS), interleukin-6 (IL-6), neurotransmitter dopamine (DA), serotonin (5-hydroxytryptamine, 5-HT), and glutamate (GLU), were measured in blood serum and brain homogenates. The results showed a significant positive effect on social interaction in the VPA rat ASD model fed GM. Blood serum and brain samples showed a positive increase in TBARS in the VPA rat model fed GM, but brain and serum serotonin levels were lower in both VPA-GM and VPA-CM groups. Dopamine in serum was also lower in the VPA-CM group than in the VPA-GM group. IL-6 levels were slightly lower in the VPA-GM group than in the VPA-CM group. In comparison with cow’s milk, goat’s milk was effective in ameliorating the neurotoxic effects of VPA. Goat’s milk may be considered a suitable source of dairy for children diagnosed with ASD. Autistic children with allergies to cow’s milk could possibly convert to goat’s milk. Nevertheless, more in-depth studies and clinical trials are recommended.